FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA DALAM PEMBELAJARAN IPAS PADA KELAS V DI SDN 167 PEKANBARU - Rizky Aisnania; Elpri Darta Putra (STKIP Subang, 2026)
This study aims to describe the factors influencing students' interest in learningscience in fifth-grade students at SDN 167 Pekanbaru. The method used in thisstudy is qualitative. This research will be conducted at SDN 167 Pekanbaru. Datacollection techniques consist of three stages: observation, interviews, anddocumentation. Data validity uses triangulation: source triangulation, technicaltriangulation, and time triangulation. Data analysis uses a descriptive qualitativeapproach consisting of three stages: data reduction, data presentation, andconclusion drawing. The results show that students' interest in learning is influencedby two main factors: internal factors and external factors. Internal factors thatinfluence student interest in learning include intelligence, interest, motivation, andattention. Each student has different abilities, interests, motivation, and attentionlevels during science learning. These differences influence students' levels ofactivity, involvement, and ability to understand the learning material. External factorsinclude teacher teaching methods, learning media, parental support, and peersupport. The use of varied learning methods, the use of appropriate learning media,parental support for learning activities, and positive interactions between peers cancreate a more active, engaging, and enjoyable learning environment, therebyencouraging increased student interest in science.